Putative role of TMEM165 in congenital cardiomyopathies - Gonçalves, Paula P. (Frontiers in Molecular Neuroscience, 2026)
Within the significant worldwide causes of mortality and morbidity are congenital heart diseases. Congenital cardiomyopathies include conditions in which early diagnosis and care can improve survival and health. In general, the first diagnostic tool is clinician suspicion followed by appropriate imaging, classically an echocardiogram. Cardiomyopathies have high rates of clinically detectable genetic causes. In view of this, prompt genetic testing is highly recommended for patients with cardiomyopathy. Genetic diagnosis, that is relevant to both the patient and family members, can help guide the selection of appropriate therapies and provide valuable information about the presence of comorbidities in other organ systems. Congenital Disorders of Glycosylation (CDG) are a growing group of inherited multisystem disorders characterized by defects in the glycosylation of proteins and lipids. Hypertrophic / dilated cardiomyopathy and neuromuscular abnormalities are recurrent manifestations of glycosylation defects. Mutations within the gene encoding the human transmembrane protein 165 (HsTMEM165), that belong to uncharacterized protein family 0016 (UPF0016), have been associated with cases of CDG. Recent progress in basic and clinical research related to TMEM165, focusing on the pathogenicity of HsTMEM165 variants, are reviewed. Highlights include the critical role of amino acid replacement for maintaining the structural and functional integrity of TMEM165 and their known associations with phenotypes of CDG patients. Future directions in this rapidly evolving area of research are proposed, to recognize the potential involvement of HsTMEM165 in congenital cardiomyopathies.